2021
DOI: 10.21203/rs.3.rs-1208309/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Systolic and Diastolic Inter-Arm Blood Pressure Difference: A Cross-Sectional Study Of 3030 Young Healthy Adults

Abstract: More than 100 years ago, the difference in blood pressure (BP) between arms was first reported. Recent studies have shown that different blood pressure between the right and left arm leads to cardiovascular events. Three thousand and thirty volunteers participated in our study. The sIABP was equal in 163 of 3030 persons (5.37%), dIABP was equal in 222 out of 3030 persons (7.32%), from a total of 792/3030 persons (26.1%) sIAD > 10 mmHg, and dIAD > or =10 mmHg was found in 927 out of 3030 persons (33.5%) … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…These people are at risk of developing cardiovascular diseases in the future, so they need to be observed and followed up 2 The results of the Seethalakshmi et al study showed that 46% of the participants had an inter-arm SBPD of 10 mmHg or more and 35% of them had an inter-arm DBPD of 5 mmHg or more 15 . Additionally, another study showed that 26.1% of the participants had an inter-arm SBPD of 10 mmHg or more 16 . According to the studies, the difference in systolic blood pressure between the two arms is more observed in the elderly 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%
“…These people are at risk of developing cardiovascular diseases in the future, so they need to be observed and followed up 2 The results of the Seethalakshmi et al study showed that 46% of the participants had an inter-arm SBPD of 10 mmHg or more and 35% of them had an inter-arm DBPD of 5 mmHg or more 15 . Additionally, another study showed that 26.1% of the participants had an inter-arm SBPD of 10 mmHg or more 16 . According to the studies, the difference in systolic blood pressure between the two arms is more observed in the elderly 17 , 18 .…”
Section: Discussionmentioning
confidence: 99%